Addition of Bempedoic Acid to Statin–Ezetimibe versus Statin Titration in Patients with High Cardiovascular Risk: A Single-Centre Prospective Study - Giuseppe Marazzi; Giuseppe Caminiti; Marco Alfonso Perrone; Giuseppe Campolongo; Luca Cacciotti; Domenico Mario Giamundo; Ferdinando Iellamo; Paolo Severino; Maurizio Volterrani; Giuseppe Rosano (Journal of Cardiovascular Development and Disease)
Reducing levels of low-density lipoprotein cholesterol (LDL-C) below recommended thresholds is a core component of cardiovascular prevention strategies. We hypothesized that the addition of bempedoic acid to patients already on statin–ezetimibe therapy was more effective than titrating the statin dose in reducing LDL-C. The study enrolled 120 patients at high cardiovascular risk and with LDL-C above 70 mg/dL. They were randomly divided into two groups: the bempedoic acid (BA) group, taking bempedoic acid in addition to statin plus ezitimibe, and the statin titration (ST) group, including patients who doubled the dose of statin. At 12 weeks, the BA group presented a more significant decrease in LDL-C compared to the ST group (−22.9% vs. 7.5% p 0.002). The total cholesterol decreased significantly in the BA group compared to ST (−14.8% vs.−4.7%; p 0.013) No significant between-group changes in HDL and triglycerides occurred. At 12 weeks, the number of patients who reached LDL-C lower than 70 mg/dL was 38 (63%) in the BA group versus 22 (37%) in the ST group (between groups, p 0.034). In the BA group, the LDL-lowering effect of bempedoic acid was similar between patients taking atorvastatin and rosuvastatin. No side effects occurred during the follow up period. In conclusion, the addition of bempedoic acid to statin–ezetimibe combined treatment was more effective than doubling the dose of statin in reducing LDL-C levels and increased the number of patients reaching the LDL-C goal.